Spontaneous Self-Assembly of Magnetic Nanoparticle Chains, at the First Stage of a Gas Aggregation Source - Oyarzun-Medina, S (WILEY-V C H VERLAG GMBH, 2024)
There is an increasing interest in magnetic nanoparticles (MNPs) and self-assembled MNP chains for applications in biomedicine, catalysis, and other technologically relevant applications. In this work, we report the spontaneous self-assembly of MNPs at the top surface of the shield of a magnetron sputter head. The resulting nanostructures consisted of clustered nanoscale chains arranged in highly oriented microfibers, with lengths of micrometer order and diameters ranging from 20 to 600 nm. The intense magnetic field gradient around the sputter magnetron s head is the driving force of the self-assembly process, also trapping species that would otherwise be lost in the carrier gas flow. We show the spontaneous self-assembly of magnetic nanoparticles into chains and microfibers. They are formed at the top surface of the shield of a magnetron sputter head. image